Functioning of banks is with foreign capital in countries of East and Сentral Europe - Stubaylo, Tetiana (Skhid, 2013)
In the article the basic aspects of functioning of bank institutions are reflected with a foreign capital in the countries of Central and East Europe and in Ukraine. Basic pre-conditions and factors of creation of banks are exposed with participation of foreign capital, their roles in becoming and development of the national bankings systems, mainly in countries with a transitional economy, especially taking into account the consequences of financial crisis.